A Redescription of Lutzomyia (Nyssomyia) intermedia (Lutz & Neiva, 1912), and Resurrection of L. neivai (Pinto, 1926) (Diptera, Psychodidae, Phlebotominae) - CB Marcondes (Memorias do Instituto Oswaldo Cruz, 1996)
Lutzomyia (Nyssomyia) intermedia (Lutz & Neiva) is redescribed, a neotype is designated, and a very similar species, L. (N.) neivai (Pinto, 1926), is resurrected; the male and the female are redescribed. The two species can be differentiated by differences in the spermathecae, common ducts and number of cibarial horizontal teeth of the females and in the size and proportions of several structures of both sexes. The known geographical distribution of both species is given.